Hans Kelsen's Concept of Normative Imputation. (24th February 2013) - Langford, Peter; Bryan, Ian
Abstract This article compares and contrasts Hans Kelsen's concept of normative imputation, in the Lecture Course of 1926, with the concepts of peripheral and central imputation, in The Pure Theory of Law of 1934. In this process, a wider and more significant distinction is revealed within the development of Hans Kelsen's theory of positive law. This distinction represents a shift in Kelsen's philosophical allegiance from the Neo‐Kantianism of Windelband to that of Cohen. This, in turn, reflects a broader disengagement of The Pure Theory of Law from the more direct connection with a political project of a civitas maxima envisaged by the Lecture Course.